Electrochemical characterization of a Porphyridium cruentum-modified carbon paste electrode by cyclic voltammetry. Issue 4 (4th July 2018) - Zaib, Maria; Athar, Muhammad Makshoof
ABSTRACT: A carbon paste electrode was modified with red algal specie of Porphyridium cruentum and then characterization of its electrocatalytic activity was demonstrated with cyclic voltammetric studies of potassium ferricyanide (K3 [Fe(CN)6 ]) system. Stable and fast response of modified electrode to redox couple of [Fe(CN)6 ] 3− /[Fe(CN)6 ] 4− was highlighted by performing experiments in comparison to bare carbon paste electrode. Fourier transform infrared spectra revealed the functional moieties of bare and modified electrode. Electrochemical surface area and surface coverage capacity were calculated for both electrodes. The effect of scan rate helped evaluate the nature of electrode process, electron transfer mechanism, and kinetic parameters (rate constant, charge transfer coefficient).